A Quality Assurance Evaluation of Hydromorphone Adverse Events Post-Implementation of a Safety Initiative - Purivatra, Elsa; Haluk-McMahon, Charlene; El-Masri, Maher; Yrigoyen-Dacruz, Lidia; Duronio, Antoinette (University of Waterloo, 2019)
Purpose: Hydromorphone is a potent opioid that may lead to respiratory and central nervous system depression prompting naloxone use. The primary objective of this study was to evaluate whether a safety initiative implemented at Windsor Regional Hospital involving interchanging hydromorphone intravenous or subcutaneous doses of 1 mg or greater to low dose (0.5 mg) in opioid naïve, medical and surgical patients was associated with naloxone events. The secondary objective was to assess whether there was a compromise in patient pain control with the low dose. Methods: We conducted a retrospective, multicenter, observational study of medical and surgical opioid-naïve patients admitted to Windsor Regional Hospital who received intravenous or subcutaneous hydromorphone within an eighteen-month timeframe. To determine if there is an association between naloxone events and implementation of the safety initiative, we compared patients who experienced a naloxone event (cases) with patients who did not experience a naloxone event (controls) in approximately 1:4 ratio. Efficacy outcomes assessed changes in patient pain control before and after interchange policy implementation (i.e. need for increase in dose, frequency or additional analgesics). Results: Of the 4343 patients who received hydromorphone, 143 opioid naïve patients were included in the final analysis. Of the 27 patients who experienced a naloxone event, 0% of patients were interchanged. In contrast, of the 116 patients who did not experience a naloxone event, 52% were interchanged (OR = 0, 95% 0 to 0.13, p<0.01). There were no significant differences in terms of patient pain control before and after interchange policy implementation. Conclusions: The pharmacist-led safety initiative of interchanging all opioid naïve patients to low dose hydromorphone was not associated with naloxone events and did not compromise patient pain control.
Keywords: hydromorphone; naloxone; opioid; safety; pain management